2022
DOI: 10.37880/cumuiibf.989475
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Corporate Social Responsibility and Financial Performance in the Banking Sector: The Case of Turkey

Abstract: The aim of this research is to identify the socioeconomic determinants of divorce in Turkey and four sub regions in the 2008-2017 period by the panel data analysis. Also, this research examine whether the female employment on divorce differs by sector or not. According to analysis findings, per capita income level, female employment in agriculture sector, female education level and male unemployment level have a positive effect on divorce across the Turkey. These impacts differ between regions classified by so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
6

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 21 publications
0
1
0
6
Order By: Relevance
“…Bu araştırmanın bağlamında incelenen çalışmaların özeti örneklem kapsamına göre düzenlenmiş bir akışla sunulmuştur. İlk olarak, tek bir ekonomiye odaklanan çalışmalar (Chen vd., 2021;Dyduch & Krasodomska, 2017;Indrianingsih &Agustina, 2020;Özçelik, Avcı Öztürk & Gürsakal, 2014;Salah & Salama, 2016;Sharma, Panday & Dangwal, 2020;Vitezić, Vuko & Mörec, 2012;Yıldırım, Uzun Kocamış & Kuzu, 2018)…”
Section: Literatür öZetiunclassified
See 3 more Smart Citations
“…Bu araştırmanın bağlamında incelenen çalışmaların özeti örneklem kapsamına göre düzenlenmiş bir akışla sunulmuştur. İlk olarak, tek bir ekonomiye odaklanan çalışmalar (Chen vd., 2021;Dyduch & Krasodomska, 2017;Indrianingsih &Agustina, 2020;Özçelik, Avcı Öztürk & Gürsakal, 2014;Salah & Salama, 2016;Sharma, Panday & Dangwal, 2020;Vitezić, Vuko & Mörec, 2012;Yıldırım, Uzun Kocamış & Kuzu, 2018)…”
Section: Literatür öZetiunclassified
“…Sürdürülebilirlik raporlaması düzeyinde sektör ve dönem etkisini birlikte kontrol eden (Abdul Rahman & Alsayegh, 2021), sadece sektör etkisini (Baldini vd, 2018;Sharma, Panday ve Dangwal, 2020: 211) veya yıl etkisini kontrol eden (Crespi & Migliavacca, 2020;El Khoury, Nasrallah & Alareeni, 2023;Özçelik, Avcı Öztürk & Gürsakal, 2014) araştırmalar da bulunmaktadır. Bu çalışmalar, firmanın faaliyet gösterdiği sektörün ve analiz yıllarının ESG düzeyiyle ilişkisini incelemiştir.…”
Section: H5 öLçek Esg Bilgi Paylaşımı Ile Pozitif Ilişkilidirunclassified
See 2 more Smart Citations
“…Other studies (Hamilton et al, 1993; Halbritter & Dorfleitner, 2015; Humphrey et al, 2012a, 2012b) have revealed that CSR does not affect investment performance. Furthermore, there are limited studies (Alper & Aydoğan, 2018; Aras et al, 2010; Arsoy et al, 2012; Başar, 2014; Özçelik et al, 2014; Sakarya et al, 2014) on CSR in Turkey. A majority of these investigations focus on the connection between CSR and financial performance and reveal conflicting outcomes.…”
Section: Introductionmentioning
confidence: 99%